Cyberbullying and Victimization and Youth Suicide Risk: The Buffering Effects of School Connectedness. (August 2020) - Kim, JaHun; Walsh, Elaine; Pike, Kenneth; Thompson, Elaine A.
Bullying has been linked to adolescent suicidal behavior. With dramatic increases in social media use among youth, understanding the influence of cyberbullying on adolescent suicidal behavior has become central to prevention efforts. This study examined the potential protective role of school connectedness in the relationship between cyberbullying and suicide risk behavior. Data were from 93 adolescents participating in a longitudinal study of an intervention to prevent health-risk behavior including suicidal behavior. Hierarchical logistic regression was used to examine the influence of cyberbullying and school connectedness on adolescent suicidal behavior. Findings indicated that being a victim of cyberbullying, but not a perpetrator, was associated with increased risk of suicide and that connections to school moderated this relationship in that, among youth who were victims of cyberbullying, those more connected to school were less likely to report suicidal behavior. Implications for school-based suicide prevention and school nurse practice are discussed.